Settler Colonialism (Without Settlers) and Slow Violence in the Gaza Strip - Pace, Michelle; Yacobi, Haim (PARTECIPAZIONE E CONFLITTO, 2021)
Israel’s ongoing settler colonialism in occupied Palestinian territory impacts Palestinians’ everyday life in all its aspects. In this article we demonstrate how Israel’s interventions, in particular since its "withdrawal" from the Gaza Strip in 2005, can be conceptualized through a combined lens of settler colonialism and slow violence. We suggest that settler colonial violence and strategies of carceration, exploitation and elimination of the existing population - without the physical presence of settlers inside Gaza - is not only inherent in the production of a new reality and geography, but also at the core of the transformation of life of Gazans into non-life. While Israel has fewer and weaker moral obligations over Gaza’s population, at the same time it creates the possibility of manipulating destructive power and violent practices. With a specific focus on Israel’s interventions in the field of health, we examine how power, violence and health are entangled in conflict zones in general and in Gaza in particular, by documenting and critically analysing the effect of violence in general and infrastructure demolition in particular, on the everyday life of Gazans. We conclude that Israel’s withdrawal marks not only a continuation but even a radicalization of settler colonialism in the Gaza Strip through (often) slow violence.